Positron scattering from noble gases - Fursa, Dmitry; Bray, Igor (2012)
We have extended the nonrelativistic convergent close-coupling (CCC) method to the calculation of positron scattering from noble gases within the single-centre approximation. Good agreement is found with the available measurements of total cross sections and elastic differential cross sections for Ne, Ar, Kr and Xe.